Inside Al Qaeda : global network of terror - Gunaratna, Rohan, 1961- (Columbia University Press, 2002)
Based on five years of research, it sheds crucial new light on Al Qaeda's role in financing and training terrorists in Asia, Africa, the Caucuses, the Balkans, and the West and assesses the terror network's future in the wake of September 11.